EXPLORING THE IMPLEMENTATION OF TIKTOK VIDEO PROJECT ON STUDENTS’ SPEAKING PERFORMANCE - Rahmah Julianti (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2023)
This study aims to explore the implementation of Tiktok video project in improving speaking skills to provide a more profound comprehension of how TikTok videos impact students' performance by acknowledging the aspects of speaking and the students’ issues in speaking. This study applied qualitative research. There were 36 students involved in the observation on their speaking ability and 17 students were interviewed randomly to explore the students’ perceptions. The implementation of Tiktok video project yielded enhancements in the students’ speaking performance encompassing various aspects such as pronunciation, grammar, vocabulary, comprehension, and fluency. Based on the observation and the students’ perspectives, the progress of the aspects was predominantly attributed to the heightened motivation and increased confidence exhibited by the students which prompted a greater focus, extended study efforts and increased practice. Thus, the utilization of the TikTok video project is particularly well-suited for application in speaking classes, especially benefiting students with lack of motivation and confidence.